Where to Belong - Esses, Victor (Oberon modern plays, 2019)
What makes a home for you' Victor Esses is Jewish-Lebanese, Brazilian, and gay. In 1975, Victor's mother flees Lebanon as a refugee of the Civil War. In 2017, Victor visits Lebanon for the first time. In 2018, amidst the elections that will see Brazil choose a far-right president, he travels from London to SAo Paulo to show his partner the city of his childhood. Where to Belong is the tender, moving story of these journeys ' an exploration of how to find your place in a rich and complex world of identities.